PENGEMBANGAN MODUL MATEMATIKA MENGGUNAKAN MODEL PEMBELAJARAN TIME TOKEN UNTUK MENINGKATKAN KOGNITIF KOMPREHENSIF DAN PROBLEM SOLVING SISWA - Desi Nur Fitriani; Netriwati; Hasan Sastra Negara (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine the effectiveness of mathematics modules based on the Time Token learning model in enhancing students’ comprehensive cognitive abilities and problem-solving skills. The background of this research stems from the need for instructional strategies that promote active participation, critical thinking, and equitable student engagement—particularly in mathematics, a subject often perceived as abstract and challenging. The Time Token model was selected for its ability to foster a structured and cooperative learning environment that ensures fair communication among students. A quasi-experimental method was employed using a pretest-posttest control group design. The sample consisted of two experimental groups: a large group and a small group, both utilizing mathematics modules integrated with the Time Token approach. Research instruments included cognitive tests, problem-solving assessments, and student interest questionnaires. The findings revealed statistically significant improvements in both comprehensive cognitive skills and problem-solving abilities among students in both experimental groups. These results indicate that mathematics modules incorporating the Time Token model are effective in enhancing learning quality and fostering higher-order thinking competencies. The study recommends broader implementation and teacher training to support successful adoption across various educational levels and contexts.